Odpowiedź :
Odpowiedź:
i)
[tex] \frac{x - 4}{2} - 3 = 2 + x[/tex]
[tex]2 \times \frac{x - 4}{2} - 3 \times 2 = 2(2 + x)[/tex]
[tex]x - 4 - 6 = 4 + 2x[/tex]
[tex]x - 10 = 4 + 2x[/tex]
[tex]x - 2x = 4 + 10[/tex]
[tex] - x = 14[/tex]
[tex]x = - 14[/tex]
j)
[tex] \frac{x + 2}{3} - 1 = 4 - \frac{x + 1}{3} [/tex]
[tex]3 \times \frac{x + 2}{3} - 1 \times 3 = 3 \times 4 - \frac{x + 1}{3} \times 3[/tex]
[tex]x + 2 - 3 = 12 -( x + 1)[/tex]
[tex]x - 1 = 12 - x - 1[/tex]
[tex]x + x = 11 + 1[/tex]
[tex]2x = 12[/tex]
[tex]x = 6[/tex]
[tex]Zadanie\\\\i)\\\\\frac{x-4}{2}-3=2+x\ \ \ \mid\cdot2\\\\x-4-6=4+2x\ \ \ \mid-2x\\\\-x-10 =4\ \ \ \mid+10\\\\-x=14\ \ \ \mid\cdot(-1)\\\\x=-14\\\\j)\\\\\frac{x+2}{3}-1=4-\frac{x+1}{3}\ \ \ \mid\cdot3\\\\x+2-3=12-(x+1)\\\\x-1=12-x-1\ \ \ \mid+1\\\\x=12-x\ \ \ \mid+x\\\\2x=12\ \ \ \mid:2\\\\x=6[/tex]